Plan de mejoramiento empresarial para la empresa Mangueras y Conducciones S.A (2015)
This paper presents the development of MAYCO SA improvement plan. The Company is dedicated to the manufacture of black hose in low density polyethylene addressed to the agricultural and mining sector nationwide. The improvement plan is an instrument that serves to enhance and consolidate processes of change that allow build or improve vision of entrepreneurs; together with tools such as are organization, control, planning, among other things, facilitating the development of the activities of the organization. It also consists of variables that maintain continuous improvement as strategies, customers, human resources and economic development. What is presented in the following document is an improvement plan for the company MAYCO SA using the model of strategic management which will be focused on improving the processes of the areas of the organization; identifying weaknesses and threats on them by a diagnosis to determine the possible causes of the same preserving the strengths found. Starting from this study is intended to strengthen the company to be in continuous improvement and allows become more competitive not only locally but also at national level.